Thermal modelling of selective beam melting processes using heterogeneous time step sizes - Soldner, Dominic; Mergheim, Julia (Computers & Mathematics with Applications, 2019)
In the context of powder bed-based additive manufacturing, complex part geometries are realised in a layer-by-layer fashion and by the fusion of powdered material in locally defined regions by means of e.g. a laser or electron beam. Simulating these manufacturing processes from a macroscopic point of view may lead to computationally expensive models, due to different scales in space and time, highly non-linear material behaviour and methods to account for the layer-wise build, i.e. dynamic growth of the computational domain. Aiming towards a reduction of the computational cost multiple numerical methods are therefore combined.
CRIS-Team WoS Importer:2019-10-15